IMPLEMENTASI PENGEMBANGAN SUMBER DAYA MANUSIA DALAM UPAYA MENINGKATKAN KOMPETENSI KINERJA KARYAWAN DI PT. JALUR NUGRAHA EKAKURIR COUNTER AGEN PARK ROYAL SIDOARJO - Aisya Amalia; Lafaifa Wibawa; Adam Alfino Ramadoni; Muhammad Khoirul Huda; Fakhrudin Alimi; Ayu Lucy Larassaty (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
One of the important factors in the success of a company in achieving its vision and mission is the quality of Human Resources (HR). The purpose of this study was to determine the importance of implementing human resource development in an effort to improve employee performance competencies. This study observes the application of Human Resources in the management of PT. Nugraha Ekakurir Trail Agent Counter Park Royal Sidoarjo. The research method used is an approach with a descriptive method. Data collection techniques for interviewee questions then the results are used for company analysis. The results of the study identified that the implementation of human resource development at the JNE Park Royal sales counter, namely on-the-job training, education/training and seminars at the central JNE company, had an impact on increasing employee performance competencies, it can be said that human resource development must continue to be implemented to maintain the company's performance and turnover remained stable and even increased. Keywords: HR management, performance competence